(untitled) (Tribhuvan University Journal of Microbiology, 2023)
Objectives: The purpose of the study was to determine the extent of antibiotic-resistant E. coli in various sacred ponds of Janakpurdham. Methods: A cross-sectional study was conducted and 16 samples were processed from 16 different revered ponds around Janakpurdham. Isolation of E. coli was done through cultural and biochemical analysis. Kirby-Bauer disc diffusion test was employed to test the susceptibility of isolates to antibiotics. Results: A total of 16 E. coli isolates, one from each sampling site, were analysed for their antibiotic-resistant pattern against the eight most commonly used antibiotics. From the total samples, 100% (16) were sensitive to tetracycline, Ciprofloxacin, Amikacin, and Gentamicin while 88% (14), 25% (4), 62% (10), and 44% (7) were resistant to Ampicillin, Amoxycillin/Clavulanate, Cefotaxime and Ceftazidime respectively. Two isolates had the lowest estimated multiple antibiotic resistance index (0.125). In addition, 10 isolates showed indices ranging from 0.25 to 0.375. Two isolates showed the highest indices i.e., 0.5. Conclusion: The holy ponds of Janakpurdham were found to be highly contaminated with pathogenic bacteria. The results may indicate the origin of E. coli isolates from an area of high antibiotic use.